2017
DOI: 10.1128/mbio.01237-17
|View full text |Cite
|
Sign up to set email alerts
|

The Human Salivary Microbiome Is Shaped by Shared Environment Rather than Genetics: Evidence from a Large Family of Closely Related Individuals

Abstract: The human microbiome is affected by multiple factors, including the environment and host genetics. In this study, we analyzed the salivary microbiomes of an extended family of Ashkenazi Jewish individuals living in several cities and investigated associations with both shared household and host genetic similarities. We found that environmental effects dominated over genetic effects. While there was weak evidence of geographical structuring at the level of cities, we observed a large and significant effect of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 37 publications
7
96
0
1
Order By: Relevance
“…The differences of microbiomes for the same individual at different time points are significantly lower in the oral cavity than in the gut, skin and other body parts [18]. The effects of the early living environment on shaping oral microbes are much more than genetic factors [19]. In addition, lifestyle habits, social factors, and oral pH value also affect the composition of the oral microbiome [20].…”
Section: Introductionmentioning
confidence: 99%
“…The differences of microbiomes for the same individual at different time points are significantly lower in the oral cavity than in the gut, skin and other body parts [18]. The effects of the early living environment on shaping oral microbes are much more than genetic factors [19]. In addition, lifestyle habits, social factors, and oral pH value also affect the composition of the oral microbiome [20].…”
Section: Introductionmentioning
confidence: 99%
“…In one of three published oral microbiome twin studies 19,20,22 , MZ twin pairs were found to be no more similar than DZ twin pairs, and they became less similar when they no longer cohabited 22 . Kissing couples were observed to share highly similar tongue dorsum microbial communities 23 , and shared household was more important than genetic relationship in a dataset from an extended family 24 . Another study found that household members, particularly couples, shared more of their microbiota than individuals from different households 25 .…”
Section: Discussionmentioning
confidence: 98%
“…The microbiome is also personal – gut microbiome samples can be used to uniquely identify individuals from groups of hundreds of others (Franzosa et al., ) – but generally this identifiability decreases with time because the human microbiome is a changing ecosystem that varies with external factors. For example, individuals who live together share more similar microbiomes (Shaw et al., ; Song et al., ) and events like moving abroad or diarrheal illness alter the microbiome (David et al., ). The microbiome therefore contains implicit information about not only individuals’ lifestyles (e.g., their diet and drug intake) but, crucially, social relationships between individuals (e.g., shared households and interaction patterns) (Rothschild et al., ).…”
Section: More‐than‐human Surveillance and Microbial Noisementioning
confidence: 99%